Compost obtained from feces of dairy cattle vs. fertilizer on triticale production (X Triticum secale Wittmack) - Beltrán Santoyo, Miguel Ángel; Álvarez Fuentes, Gregorio; Pinos Rodríguez, Juan Manuel; García Lopez, Juan Carlos; Castro Rivera, Rigoberto (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
The use of compost obtained from feces is increasingly common in agriculture for soil fertility, the objective of this study was to determine the plant height, number of stems per m2, leaf length, number of leaves per stem and dry matter yield of triticale (X Triticum secale Wittmack), fertilized with compost (humus and humic acids) and urea. A complete randomized design was used with 6 treatments and 3 replications in experimental units of 60 m2 and seeding density of 100 kg of seed per ha. The treatments were: humus, humic acids, urea, humus + urea, humic acids + urea and control. The higher production indicate that the combination of organic and inorganic fertilizationwas better than the other treatments (p 0.05). The production of triticale in treatments with urea was up to 70% higher than the control and anothers treatments evaluated.